Social Recognition in the Protecting of Land Ownership in Ngadisari Village - Zainal Fadri (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2020)
This study aims to explore the role of the community in protecting land. Land in the Tengger community has been the spotlight since an increase in tourist visits to the Bromo area, which has raised many questions and curiosity about the land preservation model. In collecting data and analysis, the researcher used a qualitative descriptive approach. It was further carried out in-depth interviews with several key informants to answer the research question. The research results show that the productive soil conditions make the Tengger community closely prevent the land from living sustainably. Land conditions supported by the community in understanding traditional values as a legacy from their ancestors discouraged people from selling because this is a prohibition unviolated. The Ngadisari’s Village Government has made an effort to protect the land in response to the challenges of buying and selling land by issuing customary regulations with recognition. The traditional rules regarding the prohibition of the land of sale become legal rules and have legal force.